A mechanistic review of lithiophilic materials: resolving lithium dendrites and advancing lithium metal-based batteries. (6th July 2021) - Cha, Eunho; Yun, Jong Hyuk; Ponraj, Rubha; Kim, Do Kyung
Abstract : A review and the prospect of lithiophilic materials to highlight their versatility among the various forms of lithium metal-based batteries. Abstract : Over the past decades, there has been tremendous progress to overcome the intrinsic issues of lithium metal batteries (LMBs). Indeed, the advanced designs of lithium (Li) hosts, protection layers, and solid-state electrolytes (SSEs) are widely utilized for high-performing LMBs to address the issues of unstable solid–electrolyte-interphase (SEI) and Li dendrites. However, the poor lithiophilicity exhibited by most of those designs cannot regulate the initial Li nucleation, which leads to a non-uniform Li deposition that inevitably causes dendrite growths. Recent years have seen a growth of investigations into regulating the nucleation overpotential of Li by enhancing lithiophilicity. In particular, the utilization of lithiophilic materials, which allows for the effective control of nucleation sites to stabilize Li deposition, has emerged as an essential strategy to enhance lithiophilicity in LMBs. Nevertheless, a comprehensive overview of lithiophilic materials for advanced LMBs is still absent. In this review, we cover a wide range of lithiophilic materials that are successfully implemented as a component for Li hosts, as a protective layer for bulk Li foils, and as an interface mediator between Li and SSEs. We also present opportunities and prospects for the future development of lithiophilic materials for safe and practical LMBs.